MILITARY-PATRIOTIC SOVIET YOUTH'S EDUCATION ARRANGEMENT IN 1920s (BASED ON DOCUMENTS OF THE STAVROPOL REGION) - T. A. Dvortsova (Гуманитарные и юридические исследования)
The article studies the organization and development of military-patriotic education of the Soviet youth in the 1920s. During this period, the Soviet authorities delegate the main function of youth military patriotic education to city department of general military education of the population - Vsevobuch. The stages of development and results of the work of this organization are analyzed. The author pays special attention to the role of a school instructor in the ield of school construction. The article notes a signiicant contribution of the youth military and sports organizations in forming «the new Soviet person».